1997
DOI: 10.1101/gad.11.4.451
|View full text |Cite
|
Sign up to set email alerts
|

A role for bone morphogenetic proteins in the induction of cardiac myogenesis.

Abstract: Little is known about the molecular mechanisms that govern heart specification in vertebrates. Here we demonstrate that bone morphogenetic protein (BMP) signaling plays a central role in the induction of cardiac myogenesis in the chick embryo. At the time when chick precardiac cells become committed to the cardiac muscle lineage, they are in contact with tissues expressing BMP-2, BMP-4, and BMP-7. Application of BMP-2-soaked beads in vivo elicits ectopic expression of the cardiac transcription factors CNkx-2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
529
3
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 634 publications
(572 citation statements)
references
References 71 publications
(75 reference statements)
27
529
3
8
Order By: Relevance
“…However, to date, no small regulator targeting the myocardial fibrosis was reported. BMP-7 has been reported to be involved in cardiac myogenesis of chick embryo, and BMP signaling pathways are functional in cardiac myocytes from mice, rats, and humans (Schultheiss et al 1997;Wu et al 2014). To Relative mRNA expression levels of collagen3.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no small regulator targeting the myocardial fibrosis was reported. BMP-7 has been reported to be involved in cardiac myogenesis of chick embryo, and BMP signaling pathways are functional in cardiac myocytes from mice, rats, and humans (Schultheiss et al 1997;Wu et al 2014). To Relative mRNA expression levels of collagen3.…”
Section: Discussionmentioning
confidence: 99%
“…BMP2/4 are critical for cardiomyocyte induction and are expressed in anterior lateral plate endoderm and ventral mesoderm (Lyons et al, 1995;Schultheiss et al, 1997). BMP signaling appears to be interacting and coordinated with the canonical Wnt signaling wave, as it progresses anteroposteriorly across the bilateral heart fields.…”
Section: Dorsal Wnt Inhibitory Activity Is Coordinated With Ventral Bmentioning
confidence: 99%
“…The cardiac-promoting activities of these molecules appear to correlate with their involvement in normal cardiogenesis in the embryo. In situ hybridization data in the developing chick, frog, and/or mouse has shown that BMP2, BMP4, FGF4, FGF8, WNT11, Dkk1, and crescent are expressed at the right time and place to act as primary stimulators of heart formation in the developing embryo (Kispert et al, 1996;Schultheiss et al, 1997;Shibata et al, 2000;Niehrs et al, 2001;Alsan and Schultheiss, 2002). Moreover, specific inhibition of the expression and/or activity of WNT11 or BMP can significantly diminish the formation of cardiac tissue in the vertebrate embryo (Schultheiss et al, 1997;Schlange et al, 2000;Pandur et al, 2002).…”
Section: Specification Of Precardiac Mesoderm Cellsmentioning
confidence: 99%